Cultural taboo and the limits of the mind in the novel Jedan razoren um (A certain degraded mind) by Lazar Komarčić. The medicalization of madness and the changes in Serbian literature at the end of the 19th century - Nowak-Bajcar, Sylwia (Poznańskie Studia Slawistyczne, 2025)
In this article, Lazar Komarčić’s novel Jedan razoren um from 1893 is presented as a text inaugurating the literary discourse devoted to the medicalization of madness. The authors of the previous discussions of this novel have highlighted the issue of tabooing madness, without paying attention to the fact that it is the first work in Serbian literature whose author, going beyond the boundaries of cultural taboo, described the space of a Belgrade insane asylum. The method of artistic articulation of madness (a pathological figure) and a psychiatric hospital (infirmerium) determines the groundbreaking importance of Komarčić’s novel as a starting point for research on the impact of the development of medicine on the cultural perception of the disease in Serbia and the development of Serbian modernism.